2002
DOI: 10.1067/mtc.2002.118682
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of endoscopic versus conventional harvesting of the saphenous vein in coronary artery bypass surgery

Abstract: In this prospective randomized trial, endoscopic harvesting of the saphenous vein significantly reduced postoperative leg wound complications, including infection, and improved patient satisfaction as compared with the conventional harvesting technique. There were no significant histologic differences between the conventional and endoscopically harvested saphenous veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 20 publications
5
105
1
4
Order By: Relevance
“…Various papers have cited vein procurement time for two lengths of conduit using open vein harvest of 32-64.4 min and using endoscopic vein harvesting of 27.6-65 min. 2 The evidence is largely inconclusive on which is the quicker technique. Certainly there is a learning curve to be surmounted in mastering either.…”
Section: Discussionmentioning
confidence: 99%
“…Various papers have cited vein procurement time for two lengths of conduit using open vein harvest of 32-64.4 min and using endoscopic vein harvesting of 27.6-65 min. 2 The evidence is largely inconclusive on which is the quicker technique. Certainly there is a learning curve to be surmounted in mastering either.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies have shown that patients undergoing EVH have significantly less wound pain, fewer complications, fewer mean days until ambulation, a shorter hospital stay, better cosmetic results, and greater overall patient satisfaction [1][2][3][4][5][6]. The outpatient clinic visits for wound complications were significantly fewer after endoscopic than after traditional vein harvest [7].…”
Section: Discussionmentioning
confidence: 99%
“…4 Compared with open vein-graft harvesting, endoscopic harvesting has many advantages including better cosmetic appearance, less pain, and fewer infections, resulting in decreased length of hospital stay postoperatively and fewer readmission for leg wound infections. 5,6 Endoscopic and open vein-graft harvesting have been shown to have similar initial short-term survival and patency rates. 7,8 In 2009, a widely publicized study of 3000 patients by Lopes et al 9 raised the concern that compared with open veingraft harvesting, endoscopic harvesting was associated with a 50% increase in mortality and a composite 22% increase in death, myocardial infarction, and revascularization at 3 years following the procedure.…”
Section: Espite a Decrease In Utilization Rate Duringmentioning
confidence: 99%